Utilization of modified NFL combine testing to identify functional deficits in athletes following ACL reconstruction - Myer, G. D.; Schmitt, L. C.; Brent, J. L.; Ford, K. R.; Barber Foss, K. D.; Scherer, B. J.; Heidt Jr., R. S.; Divine, J. G.; Hewett, T. E. (Journal of Orthopaedic & Sports Physical Therapy, 2011)
STUDY DESIGN: Case control. OBJECTIVES: To use modified NFL Combine testing methodology to test for functional deficits in athletes following anterior cruciate ligament (ACL) reconstruction following return to sport. BACKGROUND: There is a need to develop objective, performance-based, on-field assessment methods designed to identify potential lower extremity performance deficits and related impairments in this population. METHODS: Eighteen patients (mean ± SD age, 16.9 ± 2.1 years; height, 170.0 ± 8.7 cm; body mass, 71.9 ± 21.8 kg) who returned to their sport within a year following ACL reconstruction (95% CI: 7.8 to 11.9 months from surgery) participated (ACLR group). These individuals were asked to bring 1 or 2 teammates to serve as control participants, who were matched for sex, sport, and age (n = 20; mean ± SD age, 16.9 ± 1.1 years; height, 169.7 ± 8.4 cm; body mass, 70.1 ± 20.7 kg). Functional performance was tested using the broad jump, vertical jump, modified long shuttle, modified pro shuttle, modified agility T-test, timed hop, triple hop, single hop, and crossover hop tests. A 1-way multivariate analysis of variance (MANOVA) was used to evaluate group differences for dependent performance variables. RESULTS: The functional performance measurements of skills requiring bilateral involvement of both lower extremities showed no group differences between the ACLR and control groups (P>.05). An overall group difference (P = .006) was observed for the combined limb symmetry index (LSI) measures. However, the modified double-limb performance tasks (long shuttle, modified agility T-test, and pro shuttle) were not, independently, sufficiently sensitive to detect limb deficits in individuals with ACL reconstruction. Conversely, the LSI on the distance measures of the single-limb performance tasks all provided moderate to large effect sizes to differentiate between the ACLR and control groups, as the individuals who had ACL reconstruction demonstrated involved limb deficits on all measures (P<.05). Finally, the LSI for the timed hop test was not different between groups (P>.05). CONCLUSIONS: These findings indicate that, while unilateral deficits are present in individuals following ACL reconstruction, they may not be evident during bipedal performance or during modified versions of double-limb performance activities. Isolation of the involved limb with unilateral hopping tasks should be used to identify deficits in performance.